Modified coupling agent and application thereof in photovoltaic packaging material
By preparing a modified coupling agent containing vinyl and alkoxy groups and adding it to the photovoltaic packaging material, the problem of the decreasing adhesion of traditional coupling agents during hot pressing is solved, the cross-linking degree and adhesion are improved, and the stability of photovoltaic modules in high temperature and high humidity environments is ensured.
Patent Information
- Application Number
- CN202510000353.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
In traditional photovoltaic packaging materials, silane coupling agents are prone to migrate during casting, storage and hot pressing of the adhesive film, resulting in a decrease in adhesion. Methods to increase the crosslinking degree such as increasing the crosslinking agent content will lead to bubble generation, affecting the lamination process.
A silicon-containing coupling agent containing 2-5 vinyl groups and 3-15 alkoxy groups is used to prepare a modified coupling agent by hydrosilizing reaction of methyl vinyl siloxane with hydrogen-containing silane, and added to the photovoltaic encapsulation material to improve crosslinking and adhesion.
The cross-linking and adhesion of photovoltaic packaging materials are improved, the adhesion attenuation after high temperature and high humidity aging is reduced, and the long-term stability of photovoltaic modules in harsh environments is ensured.
Smart Images

Figure BDA0005224804700000021 
Figure BDA0005224804700000022 
Figure BDA0005224804700000031
Abstract
Description
Technical Field
[0001] The invention relates to a modified coupling agent for photovoltaic packaging materials, and belongs to the technical field of photovoltaic packaging materials. Background Art
[0002] Solar cell encapsulation materials are usually composed of base resin, cross-linking agent, auxiliary cross-linking agent, coupling agent, antioxidant and other auxiliary agents, which play a bonding role for photovoltaic modules, provide structural support, provide electrical insulation and water vapor barrier, and provide excellent weather resistance. Coupling agents can react with both organic groups and inorganic surfaces, and can improve the adhesion between photovoltaic film and glass backplane in photovoltaic encapsulation materials.
[0003] With the development and large-scale application of solar photovoltaic technology, higher requirements are placed on the performance of photovoltaic modules. The packaging materials are required to have a higher degree of cross-linking and better aging resistance to cope with more demanding installation environments. For example, offshore photovoltaic projects have requirements for the moisture and heat aging resistance of photovoltaic modules.
[0004] In traditional photovoltaic film production, silane coupling agents are usually used as tackifiers. However, these small molecule coupling agents are prone to migration during the film casting, storage and hot pressing process, resulting in slippage and decreased adhesion during hot pressing. CN110079222 uses alkoxysilane oligomers as tackifiers to improve the long-lasting adhesion of packaging materials after aging.
[0005] The most common method to improve the crosslinking degree of the encapsulation film is to increase the content of the crosslinking agent, i.e., the organic peroxide. However, the peroxide will decompose into small molecules such as carbon dioxide and methanol during the high-temperature lamination process, and will produce more bubbles during the lamination process of the photovoltaic module. CN117567961B provides an ethylene / α-olefin random copolymer, which can obtain an encapsulation film with a high crosslinking degree by controlling the structure of the matrix resin. The purpose of adjusting the crosslinking degree can be achieved by adjusting the matrix resin, but strict process control is required. For example, resins with different crosslinking degrees need to be achieved by adjusting the preparation formula of the resin, which is difficult to operate in downstream applications. Summary of the invention
[0006] The object of the present invention is to provide a modified coupling agent to improve the crosslinking degree of solar packaging materials and improve the long-lasting bonding performance of the packaging materials after high-temperature and high-humidity aging.
[0007] Another object of the present invention is to propose an application of the modified coupling agent in photovoltaic packaging materials.
[0008] To achieve the above object, the technical solution of the present invention is as follows:
[0009] In one aspect, a modified coupling agent is provided, wherein the modified coupling agent has the following characteristics:
[0010] The modified coupling agent is a silicon-containing coupling agent containing 2-5 vinyl groups and 3-15 alkoxy groups; the molar ratio of the vinyl groups to the alkoxy groups of the modified coupling agent is 1:1-8; the modified coupling agent is prepared by hydrosilylation reaction of methylvinylsiloxane and hydrogen-containing silane.
[0011] As a preferred technical solution of the present invention, the methyl vinyl siloxane is linear or cyclic methyl vinyl siloxane.
[0012] Furthermore, the linear methylvinylsiloxane has a structure shown in Formula 1:
[0013]
[0014] In the formula: n=1-8, preferably 2-5.
[0015] Furthermore, the cyclic methylvinylsiloxane has a structure shown in Formula 2:
[0016]
[0017] In the formula: m=3-5, preferably 4-5.
[0018] As a preferred technical solution of the present invention, the hydrogen-containing silane has a structure shown in Formula 3:
[0019]
[0020] In the formula: X is R or OR; wherein R is an alkyl group having 1 to 8 carbon atoms.
[0021] Furthermore, the hydrogen-containing silane can be selected from one or more of trimethoxysilane, triethoxysilane, methyldimethoxysilane and methyldiethoxysilane.
[0022] In the present invention, the hydrosilylation reaction is a conventional reaction in the art. In some embodiments, the catalyst of the hydrosilylation reaction is a Custer platinum catalyst, the reaction temperature of the reaction is 60 to 150°C, for example: 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 150°C, the reaction time is 4-6h, for example: 4h, 5h, 6h; the concentration of the catalyst in the hydrosilylation reaction is 1 to 50ppm, for example: 3ppm, 5ppm, 8ppm, 10ppm, 15ppm, 20ppm, 30ppm, 45ppm.
[0023] In the present invention, the molar ratio of methylvinylsiloxane to hydrogen-containing silane is 1:1-10, preferably 1:1-5.
[0024] In the present invention, the linear methylvinylsiloxane can be prepared by conventional operations in the art, and the cyclic methylvinylsiloxane can be purchased.
[0025] The preparation method of the linear methylvinylsiloxane can be: tetramethyltetravinylcyclotetrasiloxane and tetramethyldivinyldisiloxane are uniformly mixed, nitrogen protection is passed, the temperature is raised to 60°C, trifluoromethanesulfonic acid catalyst is added, the reaction is carried out at 60°C for 6 hours, the temperature is lowered to room temperature, calcium carbonate is added to neutralize the catalyst, the mixture is stirred for 1 hour, and a colorless transparent product is obtained by filtering. The ratio of the raw materials is changed to obtain the linear methylvinylsiloxane of the desired structure.
[0026] In another aspect, the present invention provides use of the modified coupling agent in photovoltaic encapsulation materials.
[0027] Furthermore, the photovoltaic encapsulation material comprises: a modified coupling agent, a base resin, a cross-linking agent, a co-cross-linking agent, and an antioxidant.
[0028] In a specific embodiment, the amount of each component of the photovoltaic encapsulation material is:
[0029] Base resin: 100 parts by weight;
[0030] Modified coupling agent: 0.1-3 parts by weight, for example: 0.2 parts by weight, 0.4 parts by weight, 0.8 parts by weight, 1 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, preferably 0.5-2 parts by weight;
[0031] Cross-linking agent: 0.1-5 parts by weight, for example: 0.2 parts by weight, 0.4 parts by weight, 1 part by weight, 1.5 parts by weight, 2.5 parts by weight, 3 parts by weight, 4 parts by weight, 4.5 parts by weight, preferably 0.5-2 parts by weight;
[0032] Auxiliary cross-linking agent: 0.1-5 parts by weight, for example: 0.2 parts by weight, 0.4 parts by weight, 1 part by weight, 1.5 parts by weight, 2.5 parts by weight, 3 parts by weight, 4 parts by weight, 4.5 parts by weight, preferably 0.1-2 parts by weight;
[0033] Antioxidant: 0.01-1 part by weight, for example: 0.02 part by weight, 0.04 part by weight, 0.08 part by weight, 0.1 part by weight, 0.3 part by weight, 0.5 part by weight, 0.7 part by weight, 0.9 part by weight, preferably 0.05-0.5 part by weight.
[0034] Furthermore, the base resin is an ethylene-α-olefin copolymer.
[0035] Further, the cross-linking agent is a peroxide cross-linking agent, including but not limited to one or more of the following: tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl peroxy 2-ethylhexyl carbonate, tert-amyl peroxy (2-ethylhexyl) carbonate, and tert-butyl peroxy 3,3,5-trimethylhexanoate.
[0036] Furthermore, the auxiliary cross-linking agent is one or more of multifunctional acrylate substances, including but not limited to: trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, triallyl isocyanurate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, and ditrimethylolpropane tetraacrylate.
[0037] Furthermore, the antioxidant is one or more of hindered phenol or phosphate antioxidants, including but not limited to: β-[3,5-di-tert-butyl-4-hydroxyphenyl] propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], 1,2-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine, 2,2'-oxalyl-bis[ethyl-3 -(3,5-di-tert-butyl-4-hydroxyphenyl)] propionate, N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide), triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate], 4,6-bis(octylthiomethyl)-o-cresol, tris[2,4-di-tert-butylphenyl] phosphite, bis[2,4-di-tert-butylphenyl] pentaerythritol diphosphite.
[0038] Herein, the specific process of applying the modified coupling agent to the field of photovoltaic encapsulation film can be a conventional operation in the field, for example, 100 parts of the base resin, 0.5-2 parts of the modified coupling agent, 0.5-2 parts of the cross-linking agent, 0.3-2 parts of the auxiliary cross-linking agent, and 0.05-0.3 parts of the antioxidant are mixed evenly, and a twin-screw extruder is used to cast and extrude at 70-100°C. During the casting process, a mercury or halogen light source with a UV wavelength of 300-400nm is used for irradiation. The cast film is cooled, pulled, and rolled up to obtain the photovoltaic film.
[0039] Compared with the prior art, the present invention has the following technical advantages: the present invention uses methylvinylsiloxane and hydrogen-containing silane as raw materials to prepare a polyvinylpolyalkoxy silicon-containing coupling agent, which is added to solar packaging materials. On the one hand, it can improve the cross-linking degree of the packaging material, and at the same time can provide higher adhesion and reduce the adhesion attenuation after high temperature and high humidity aging. DETAILED DESCRIPTION
[0040] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0041] Source information of main raw materials of the embodiments of the present invention:
[0042] Linear methylvinylsiloxane: It can be prepared according to conventional operations in the art. The preparation method is: evenly mix tetramethyltetravinylcyclotetrasiloxane and tetramethyldivinyldisiloxane, pass nitrogen protection, heat to 60°C, add trifluoromethanesulfonic acid catalyst, react at 60°C for 6 hours, cool to room temperature, add calcium carbonate to neutralize the catalyst, stir for 1 hour, and filter to obtain a colorless and transparent product. Change the ratio of raw materials to obtain linear methylvinylsiloxane with the desired structure.
[0043] Cyclic methylvinylsiloxane: trivinyltrimethylcyclotrisiloxane, tetravinyltetramethylcyclotetrasiloxane, pentavinylpentamethylcyclopentasiloxane, Shanghai MacLean Biochemical Technology Co., Ltd.;
[0044] Hydrogen-containing silanes: trimethoxysilane, triethoxysilane, methyldimethoxysilane, methyldiethoxysilane, Shandong Sike New Materials Co., Ltd.;
[0045] Ethylene-α-olefin copolymer: The Dow Chemical Company, 8660.
[0046] Unless otherwise specified, other raw materials and reagents in the following examples and comparative examples were purchased from commercial sources.
[0047] The test methods used in the embodiments and comparative examples of the present invention are as follows:
[0048] Structural characterization of the modified coupling agent: The ratio of vinyl groups to alkoxy groups was determined using a Bruker AC300 nuclear magnetic resonance spectrometer.
[0049] Cross-linking degree test: Randomly sample 5 locations on the film sample and test the cross-linking degree according to the xylene extraction method of GB / T29848-2018. Calculate the average of the 5 cross-linking degree test values and record it as the cross-linking degree of the sample.
[0050] Adhesion test: The peel strength is used to characterize the adhesion. The greater the peel strength, the greater the adhesion of the sample. The test method refers to the national standard GB / T 2790-1995; Sample preparation: Take 3mm thick glass, packaging material, and backplane, and put them into a vacuum laminator in the order of glass / packaging material / backplane. Lamination and curing at 150℃ for 15 minutes, test on a tensile machine, the peel speed is 100mm / min, and record the tensile strength value.
[0051] High temperature and high humidity aging test: Conduct heat and humidity aging test according to GB / T2423.3. Test conditions: 85℃, relative humidity 85%, 1000h.
[0052] [Preparation Example]
[0053] Preparation of modified coupling agent A: 358 parts of linear methylvinylsiloxane with an average degree of polymerization of 2 and 122 parts of trimethoxysilane were added to the reactor, stirring was started, the temperature was raised to 100°C, 0.01 parts of Custer catalyst were added, and the reaction was carried out for 4 hours to obtain modified coupling agent A.
[0054] NMR data 1 H NMR: [d, ppm] = 0-0.5 (-Si-CH3), 0.5-1 (-Si-CH2-CH2-), 3.5-4 (-Si-OCH3), 5.5-6 (-Si-CH=CH2), the molar ratio of vinyl to methoxy is 1:1.02;
[0055] Preparation of modified coupling agent B: 444 parts of linear methylvinylsiloxane with an average degree of polymerization of 3 and 212 parts of methyldimethoxysilane were added to the reactor, stirring was started, the temperature was raised to 100°C, 0.006 parts of Custer catalyst were added, and the reaction was carried out for 4 hours to obtain modified coupling agent B.
[0056] NMR data 1 H NMR: [d, ppm] = 0-0.5 (-Si-CH3), 0.5-1 (-Si-CH2-CH2-), 3.5-4 (-Si-OCH3), 5.5-6 (-Si-CH=CH2), the molar ratio of vinyl to methoxy is 1:1.32. ;
[0057] Preparation of modified coupling agent C: 444 parts of linear methylvinylsiloxane with an average degree of polymerization of 3 and 244 parts of trimethoxysilane were added to the reactor, stirring was started, the temperature was raised to 80°C, 0.006 parts of Custer catalyst were added, and the reaction was carried out for 6 hours to obtain modified coupling agent C.
[0058] NMR data 1H NMR: [d, ppm] = 0-0.5 (-Si-CH3), 0.5-1 (-Si-CH2-CH2-), 3.5-4 (-Si-OCH3), 5.5-6 (-Si-CH=CH2), the molar ratio of vinyl to methoxy is 1:1.94. ;
[0059] Preparation of modified coupling agent D: 530 parts of linear methylvinylsiloxane with an average degree of polymerization of 4 and 492 parts of triethoxysilane were added to a reactor, stirring was started, the temperature was raised to 80°C, 0.015 parts of Custer catalyst were added, and the reaction was carried out for 6 hours to obtain modified coupling agent D.
[0060] NMR data 1 H NMR: [d, ppm] = 0-0.5 (-Si-CH3), 0.5-1 (-Si-CH2-CH2-), 1 -1.5 (-Si-OCH2CH3), 3.5-4 (-Si-OCH2CH3), 5.5-6 (-Si-CH=CH2), the molar ratio of vinyl to ethoxy is 1:2.98. ;
[0061] Preparation of modified coupling agent E: 616 parts of linear methylvinylsiloxane with an average degree of polymerization of 5 and 402 parts of methyldiethoxysilane were added to the reactor, stirring was started, the temperature was raised to 120°C, 0.015 parts of Custer catalyst was added, and the reaction was carried out for 5 hours to obtain modified coupling agent E.
[0062] NMR data 1 H NMR: [d, ppm] = 0-0.5 (-Si-CH3), 0.5-1 (-Si-CH2-CH2-), 1 -1.5 (-Si-OCH2CH3), 3.5-4 (-Si-OCH2CH3), 5.5-6 (-Si-CH=CH2), the molar ratio of vinyl to ethoxy is 1:1.45;
[0063] Preparation of modified coupling agent F: 616 parts of linear methylvinylsiloxane with an average degree of polymerization of 5 and 610 parts of trimethoxysilane were added to a reactor, stirring was started, the temperature was raised to 140°C, 0.006 parts of Custer catalyst were added, and the reaction was carried out for 5 hours to obtain modified coupling agent F.
[0064] NMR data 1 H NMR: [d, ppm] = 0-0.5 (-Si-CH3), 0.5-1 (-Si-CH2-CH2-), 3.5-4 (-Si-OCH3), 5.5-6 (-Si-CH=CH2), the molar ratio of vinyl to methoxy is 1:7.34;
[0065] Preparation of modified coupling agent G: 344 parts of tetramethyltetravinylcyclotetrasiloxane and 244 parts of trimethoxysilane were added to a reactor, stirring was started, the temperature was raised to 100°C, 0.02 parts of Custer catalyst were added, and the reaction was carried out for 5 hours to obtain modified coupling agent G.
[0066] NMR data 1 H NMR: [d, ppm] = 0-0.5 (-Si-CH3), 0.5-1 (-Si-CH2-CH2-), 3.5-4 (-Si-OCH3), 5.5-6 (-Si-CH=CH2), the molar ratio of vinyl to methoxy is 1:2.89;
[0067] Preparation of modified coupling agent H: 430 parts of pentamethylpentavinylcyclopentasiloxane and 366 parts of trimethoxysilane were added to a reactor, stirring was started, the temperature was raised to 100°C, 0.008 parts of Custer catalyst was added, and the reaction was carried out for 5 hours to obtain modified coupling agent H.
[0068] NMR data 1 H NMR: [d, ppm] = 0-0.5 (-Si-CH3), 0.5-1 (-Si-CH2-CH2-), 3.5-4 (-Si-OCH3), 5.5-6 (-Si-CH=CH2), the molar ratio of vinyl to methoxy is 1:4.41.
[0069] Example 1
[0070] Add 10g of modified coupling agent A, 9g of tert-butyl peroxyisopropyl carbonate, 5g of triallyl isocyanurate, and 2g of β-[3,5-di-tert-butyl-4-hydroxyphenyl] propionate n-octadecyl alcohol to 1000g of ethylene-α-olefin copolymer. Heat the above raw materials to 50°C and mix them evenly, add them to a single-screw extruder for melt extrusion, set the screw extruder temperature to 100°C, and the screw speed to 45rpm. After extrusion, calendering, cooling, cutting, and winding, a packaging film for photovoltaic modules is prepared.
[0071] Example 2
[0072] 5g of modified coupling agent B, 5g of 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, 20g of trimethylolpropane triacrylate, and 1g of 1,2-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine were added to 1000g of ethylene-α-olefin copolymer. The above raw materials were heated to 50°C and mixed evenly, and added to a single-screw extruder for melt extrusion. The temperature of the screw extruder was set to 100°C and the screw speed was 45rpm. After extrusion, calendering, cooling, cutting, and winding, a packaging film for photovoltaic modules was prepared.
[0073] Example 3
[0074] 8g of modified coupling agent C, 8g of tert-butyl peroxide 2-ethylhexyl carbonate, 10g of trimethylolpropane triacrylate, and 0.8g of bis[2,4-di-tert-butylphenyl]pentaerythritol diphosphite were added to 1000g of ethylene-α-olefin copolymer. The above raw materials were heated to 50°C and mixed evenly, and added to a single screw extruder for melt extrusion. The screw extruder temperature was set to 100°C and the screw speed was 45rpm. After extrusion, calendering, cooling, cutting, and winding, a packaging film for photovoltaic modules was prepared.
[0075] Example 4
[0076] 15g of modified coupling agent D, 12g of tert-butyl peroxy 3,3,5-trimethylhexanoate, 5g of trimethylolpropane triacrylate, and 1g of n-octadecylβ-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate were added to 1000g of ethylene-α-olefin copolymer. The raw materials were heated to 50°C and mixed evenly, and added to a single-screw extruder for melt extrusion. The screw extruder temperature was set to 100°C and the screw speed was 45rpm. After extrusion, calendering, cooling, cutting, and winding, a packaging film for photovoltaic modules was prepared.
[0077] Example 5
[0078] Add 10g of modified coupling agent E, 12g of tert-butyl peroxyisopropyl carbonate, 5g of triallyl isocyanurate, and 2g of β-[3,5-di-tert-butyl-4-hydroxyphenyl] propionate n-octadecyl alcohol to 1000g of ethylene-α-olefin copolymer. Heat the above raw materials to 50°C and mix them evenly, add them to a single-screw extruder for melt extrusion, set the screw extruder temperature to 100°C, and the screw speed to 45rpm. After extrusion, calendering, cooling, cutting, and winding, a packaging film for photovoltaic modules is prepared.
[0079] Example 6
[0080] Add 20g of modified coupling agent F, 15g of tert-butyl peroxyisopropyl carbonate, 5g of triallyl isocyanurate, and 1g of β-[3,5-di-tert-butyl-4-hydroxyphenyl] propionate to 1000g of ethylene-α-olefin copolymer. Heat the above raw materials to 50°C and mix them evenly, add them to a single-screw extruder for melt extrusion, set the screw extruder temperature to 100°C, and the screw speed to 45rpm. After extrusion, calendering, cooling, cutting, and winding, a packaging film for photovoltaic modules is prepared.
[0081] Example 7
[0082] 12g of modified coupling agent G, 20g of 2,5-dimethyl-2,5-(di-tert-butylperoxy)hexane, 5g of triallyl isocyanurate, and 1g of β-[3,5-di-tert-butyl-4-hydroxyphenyl]propionic acid n-octadecyl alcohol ester were added to 1000g of ethylene-α-olefin copolymer. The above raw materials were heated to 50°C and mixed evenly, added to a single screw extruder for melt extrusion, the screw extruder temperature was set to 100°C, the screw speed was 45rpm, and the encapsulation film for photovoltaic modules was prepared through extrusion, calendering, cooling, cutting, and winding processes.
[0083] Example 8
[0084] 12g of modified coupling agent H, 20g of 2,5-dimethyl-2,5-(di-tert-butylperoxy)hexane, 3g of triallyl isocyanurate, and 1g of β-[3,5-di-tert-butyl-4-hydroxyphenyl]propionic acid n-octadecyl alcohol ester were added to 1000g of ethylene-α-olefin copolymer. The above raw materials were heated to 50°C and mixed evenly, and added to a single-screw extruder for melt extrusion. The screw extruder temperature was set to 100°C and the screw speed was 45rpm. After extrusion, calendering, cooling, cutting, and winding, a packaging film for photovoltaic modules was prepared.
[0085] Comparative Example 1
[0086] The encapsulation film was prepared in a method substantially the same as that in Example 3, except that the modified coupling agent C was replaced with vinyltrimethoxysilane.
[0087] Comparative Example 2
[0088] The encapsulation film was prepared in substantially the same manner as in Example 7, except that the modified coupling agent G was replaced with vinyl triethoxysilane.
[0089] The encapsulation adhesive films prepared in the above examples and comparative examples were tested for their crosslinking degree, adhesive strength and aged adhesive strength after aging for 1000 h at 85° C. and 85% relative humidity.
[0090] Test results of embodiments and comparative examples:
[0091]
[0092]
[0093] From the comparison of the performance test data of the embodiment and the comparative example described in the above table, it can be seen that:
[0094] The present invention provides a modified coupling agent containing multiple vinyl groups and multiple alkoxy groups for photovoltaic encapsulation materials. The photovoltaic adhesive film prepared can provide a higher cross-linking degree of up to 80% or more, and at the same time can provide a higher adhesion (>250N / cm), and can reduce the adhesion attenuation after high temperature and high humidity aging, the attenuation ratio is less than 30%, so that the photovoltaic encapsulation material can still maintain good adhesion in a long-term hot and humid environment.
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A modified coupling agent, wherein the modified coupling agent has the following characteristics: The modified coupling agent is a silicon-containing coupling agent containing 2-5 vinyl groups and 3-15 alkoxy groups; the molar ratio of the vinyl groups to the alkoxy groups of the modified coupling agent is 1:1-8; the modified coupling agent is prepared by hydrosilylation reaction of methylvinylsiloxane and hydrogen-containing silane.
2. The modified coupling agent according to claim 1, characterized in that The methyl vinyl siloxane is a linear or cyclic methyl vinyl siloxane; Preferably, the linear methylvinylsiloxane has a structure shown in Formula 1: Wherein: n=1 to 8, preferably 2 to 5; and / or, Preferably, the cyclic methylvinylsiloxane has a structure shown in Formula 2: In the formula: m=3-5, preferably 4-5.
3. The modified coupling agent according to claim 1 or 2, characterized in that: The hydrogen-containing silane has a structure shown in Formula 3: In the formula: X is R or OR; wherein R is an alkyl group having 1 to 8 carbon atoms.
4. The modified coupling agent according to any one of claims 1 to 3, characterized in that: The hydrogen-containing silane is selected from one or more of trimethoxysilane, triethoxysilane, methyldimethoxysilane and methyldiethoxysilane.
5. The modified coupling agent according to any one of claims 1 to 4, characterized in that: The catalyst for the hydrosilylation reaction is a Custer platinum catalyst, the reaction temperature of the reaction is 60-150° C., and the reaction time is 4-6 hours; and / or, the concentration of the catalyst in the hydrosilylation reaction is 1-50 ppm; and / or, the molar ratio of methylvinylsiloxane to hydrogen-containing silane is 1:1-10, preferably 1:1-5.
6. Use of the modified coupling agent according to any one of claims 1 to 5 in photovoltaic encapsulation materials, characterized in that: The photovoltaic encapsulation material comprises: a modified coupling agent, a base resin, a cross-linking agent, an auxiliary cross-linking agent, and an antioxidant.
7. The use according to claim 6, characterized in that The dosage of each component of the photovoltaic encapsulation material is: Base resin: 100 parts by weight; modified coupling agent: 0.1-3 parts by weight; cross-linking agent: 0.1-5 parts by weight; auxiliary cross-linking agent: 0.1-5 parts by weight; antioxidant: 0.01-1 parts by weight.
8. The use according to claim 6 or 7, characterized in that The base resin is an ethylene-α-olefin copolymer; and / or the cross-linking agent is a peroxide cross-linking agent, including but not limited to one or more of the following: tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl peroxy 2-ethylhexyl carbonate, tert-amyl peroxy (2-ethylhexyl) carbonate, and tert-butyl peroxy 3,3,5-trimethylhexanoate.
9. The use according to any one of claims 6 to 8, characterized in that: The auxiliary cross-linking agent is one or more of multifunctional acrylate substances, including but not limited to: trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, triallyl isocyanurate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, and ditrimethylolpropane tetraacrylate.
10. The use according to any one of claims 6 to 9, characterized in that: The antioxidant is one or more of hindered phenol or phosphate antioxidants, including but not limited to: β-[3,5-di-tert-butyl-4-hydroxyphenyl] propionate octadecyl alcohol ester, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, 1,2-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl] hydrazine, 2,2'-oxalyl-bis[ethyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)] propionate, N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide), triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate], 4,6-bis(octylthiomethyl)-o-cresol, tris[2,4-di-tert-butylphenyl] phosphite, bis[2,4-di-tert-butylphenyl] pentaerythritol diphosphite.
Citation Information
Patent Citations
Ethylene / α-olefin random copolymer for photovoltaic adhesive film and its application
CN117567961B
Composition containing silicon-containing polymer and cured product thereof
CN101978008A
Solar cell sealing film and solar cell utilizing same
CN103392238A
Addition type silicone rubber with high bonding strength and preparation method thereof
CN112680180A
Packaging adhesive film and preparation method and application thereof
CN116082984A